Case report: Unusual cause of refractory hypoxemia after pacemaker lead extraction - Zhou, Jingliang; He, Jinshan; Duan, Jiangbo; Li, Xuebin (Frontiers in Cardiovascular Medicine, 2023)
A 59-year-old woman with a history of a pacemaker implanted for Ⅲ-degree atrioventricular block was admitted due to pocket infection. The atrial and ventricular leads were removed via the right femoral vein using a needle's eye snare. Hypoxemia was observed immediately after the removal of the lead. It was refractory to oxygen therapy. The pulse oxygen saturation (SpO2) showed 89% in the supine position and 77% in the upright position. However, the CTPA and pulmonary perfusion SPECT/CT imaging did not reveal any signs of pulmonary embolism. Pulmonary function tests and chest CT showed normal results. Transthoracic contrast echocardiography revealed a patent foramen ovale (PFO) and a right-to-left intracardiac shunt, no significant tricuspid regurgitation, without any signs of elevated right heart pressure or pulmonary hypertension. Hypoxemia was considered to be associated with the right-to-left shunt through PFO. The condition was relieved by percutaneous closure of the PFO. Refractory hypoxemia resulting from an intracardiac right-to-left shunt following pacemaker lead extraction is a rare but serious complication. Transthoracic contrast echocardiography helps in diagnosis. If the right-to-left intracardiac shunt through PFO persists irreversibly and the associated hypoxemic symptoms are significant, closure of the PFO is necessary. Transesophageal echocardiography also revealed the presence of a left-to-right shunt through PFO during cardiac systole. The closure of the PFO is also necessary to avoid long-term complications, such as chronic pulmonary hypertension and right heart failure.